Analysis of Family Income Factors on Diarrhea Incidence through Behavior in Tapalang (Public Health Perspective Journal, 2019)
Diarrhea is one of an endemic disease and also a potential disease of outbreaks in Indonesia, including in Mamuju, West Sulawesi, where the disease is often accompanied by death. Tapalang is a sub-district with the highest cases of diarrhea in Mamuju in recent years. This study used a case control design with a fixed disease sampling technique. The population in this study were all toddlers in Tapalang as many as 1927 people with a total sample of 60 cases and 60 controls so that a total of 120 samples. The instruments used in this study were questionnaires, checklists and observation sheets. Data were analyzed using Multivariate analysis. The results showed that there was a direct and statistically significant effect between family income on the incidence of diarrhea (b = 1.50; 95% CI = 0.319 to 2.68; p = 0.013). There was an indirect influence between family income on the incidence of diarrhea through behavior but not statistically significant (b = 0.98; 95% CI = -0.76 to 2.73; p = 0.269). There is a direct influence between behavior and the incidence of diarrhea even though it is not statistically significant (b = 0.74; 95% CI = -0.41 to 1.90 p = 0.210). The conclusions of toddlers diarrhea in Tapalang is influenced by family income. It is hoped that this research can be used as a reference for related parties in diarrhea control policies and also for mothers and toddlers' families in efforts to prevent diarrhea in toddlers.